2008
DOI: 10.1002/ajmg.a.32218
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life of children with a positive carrier status for inherited cardiovascular diseases

Abstract: Familial hypercholesterolemia, hypertrophic cardiomyopathy, and long QT Syndrome are genetic cardiovascular conditions which may lead to sudden cardiac death at a young age. Preventive measures include lifestyle modifications, medications, and/or cardiac devices. Hence, identification of carrier children can protect them for the potentially life threatening consequences at a young age. Yet, informing children about their genetic risk status and subjecting them to treatment may have negative consequences. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 24 publications
7
42
0
2
Order By: Relevance
“…24 Of note, a study assessing the impact of genetic testing in children in the context of the family found parents of LQTS children rated their child's psychological well-being as impaired, when in reality their scores were comparable to the general pediatric population. 25 Our data, therefore, aligns to the limited literature to date suggesting that there is no change in psychosocial and health status outcome following genetic testing for inherited heart diseases.…”
Section: Discussionsupporting
confidence: 87%
“…24 Of note, a study assessing the impact of genetic testing in children in the context of the family found parents of LQTS children rated their child's psychological well-being as impaired, when in reality their scores were comparable to the general pediatric population. 25 Our data, therefore, aligns to the limited literature to date suggesting that there is no change in psychosocial and health status outcome following genetic testing for inherited heart diseases.…”
Section: Discussionsupporting
confidence: 87%
“…36 Five studies, however, found nonsignificant increases in children's depressive symptoms after genetic testing for FAP 28,34,35 or hereditary cardiac disease risk. 36,38 When exploring outcomes for particular subgroups, there was some evidence to suggest that children with affected parents and those with positive results may be more at risk. One study reported that children with a mother with breast cancer were at increased risk for anxiety and depression.…”
Section: What Is the Psychological Impact Of Personal Genetic Testingmentioning
confidence: 99%
“…42 Some hoped/expected medication to help 41 Promotes psychological adjustment 17,46 and child autonomy 17,46 No behavioral problems at follow-up, 25,35 regardless of test results, 28 and decreased in some at follow-up. 35 "Good" social acceptance and bullying (P < 0.001) 38 Reduction in worry/uncertainty about future life planning (education, employment, social, and economic plans) and health planning (early or presymptomatic intervention) 3,16,17,29,43,44,46,47 Majority only thought/worried about becoming sick a 'little bit' or less. 25 Reduced worry and situational distress after negative results.…”
Section: What Is the Concordance Between Empirical Data On The Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of predictive genetic testing, most studies found no statistically or clinically significant differences in depression, 40 -42 anxiety, 40 -42 general psychological wellbeing, 43 dispositional optimism, 42 or behavioral problems and competence 40 -42 when comparing those with positive and negative test outcomes. However, the survey assessments used were generally intended for serious psychopathology and, thus, may not be sensitive to subtle nonclinical shifts in emotional wellbeing.…”
Section: Predictive Testingmentioning
confidence: 99%